Pedagogical Innovation of Game-Based Learning for 21st Century Skills in Vocational Education: A Systematic Literature Review - Raziana, Elvi; Wibawanto, Hilmawan (Universitas Sebelas Maret, 2025)
Vocational education faces the demand to equip learners with 21st century skills to cope with the changing job needs. This study aims to comprehensively explore the pedagogical innovation of Game-Based Learning (GBL) in shaping and enhancing such skills in vocational education. Using the Systematic Literature Review (SLR) method, 35 relevant articles were thematically analyzed from the Scopus database. The results showed an increasing trend in the use of GBL, especially serious games and VR simulations used in various vocational sectors such as engineering and health. GBL designs often integrate development models such as ADDIE and Discovery Learning approaches, utilizing interactive game elements for authentic scenarios. GBL is proven to significantly increase learner motivation and engagement. In addition, GBL is effective in developing 21st century skills such as logical thinking, problem solving, cognitive and affective skills, and contributes to improved academic performance. In conclusion, GBL is an effective pedagogical innovation to prepare vocational education graduates with relevant competencies for future job competition